2006
DOI: 10.1002/ijc.22176
|View full text |Cite
|
Sign up to set email alerts
|

Combined human papillomavirus DNA and human papillomavirus‐like particle serologic assay to identify women at risk for high‐grade cervical intraepithelial neoplasia

Abstract: The objective of this study was to assess the utility of a second generation human papillomavirus (HPV) virus-like particle (VLP)-based ELISA as an adjunct to HPV DNA testing to identify women at risk for high-grade cervical intraepithelial neoplasia (CIN). Participants provided blood, cervical samples and interviewer-obtained questionnaire information. HPV VLPs for types 16, 18, 33, 45 and 52 were produced using a baculovirus expression system. These highly purified VLPs were used in a polymerbased ELISA test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
10
1
Order By: Relevance
“…responses have shown that there is a strong association between HPV (mainly type 16) and cervical lesions (de Gruijl et al, 1997, Wideroff et al, 1999, Combita et al, 2002, Sasagawa et al, 1998, Sun et al, 1999, Marais et al, 2000, Einstein et al, 2007. Most have reported on both HPV DNA and VLP antibodies in all patients.…”
Section: Selected By Editorsmentioning
confidence: 92%
See 1 more Smart Citation
“…responses have shown that there is a strong association between HPV (mainly type 16) and cervical lesions (de Gruijl et al, 1997, Wideroff et al, 1999, Combita et al, 2002, Sasagawa et al, 1998, Sun et al, 1999, Marais et al, 2000, Einstein et al, 2007. Most have reported on both HPV DNA and VLP antibodies in all patients.…”
Section: Selected By Editorsmentioning
confidence: 92%
“…It has been suggested that HPV VLP serological assays may be useful as an additional tool for the identification of women at risk for high-grade cervical intraepithelial neoplasia (Einstein et al, 2007). Some of these prior studies were from populations with a high proportion of HIV infections (Marais et al, 2000) or in the third world (Combita et al, 2002), some studies only focused on dysplasia (Tabrizi et al, 2006, Wideroff et al, 1999, Einstein et al, 2007, some only on cancer (Combita et al, 2002, Sun et al, 1999. In addition, some have used a proper age matched controls (Combita et al, 2002).…”
Section: Selected By Editorsmentioning
confidence: 97%
“…Recent studies have shown that the seroprevalence of antibody to HPV 16 in children younger than 11 years is 2.4% and in unselected women of 12-59 years of age it is 13% (Dunne et al, 2005;Stone et al, 2002). In a number of case-control studies, serologic responses have shown that there is a strong association between HPV and cervical lesions (de Gruijl et al, 1997;Wideroff et al, 1999;Combita et al, 2002;Einstein et al, 2007). It has been suggested that HPV VLP serologic assays may be useful as an additional tool to identify women at risk for high-grade cervical intraepithelial neoplasia (Einstein et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous serologic studies using mainly HPV-16 VLPs (de Gruijl et al, 1997;Kirnbauer et al, 1994;Le Cann et al, 1995;Wideroff et al, 1999;Combita et al, 2002;Einstein et al, 2007) have demonstrated that infection with HPVs is followed by a serologic immune response to viral capsid proteins and that anti-VLP antibodies can be an indicator of life-time exposure to HPV infection. Seroconversion most frequently occurs between 6 and 18 months after HPV DNA detection and rarely occurs in patients with transient HPV infection (Carter et al, 2000).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation